Discourse Network Analysis on detikcom and KOMPAS.com on Nuclear Power Plants Construction in Indonesia - Zulkifli, Muhammad Yunus; Amrihani, Haresti Asysy (Jurnal Komunikasi, 2024)
This research aimed to determine the emerging discourse regarding the construction of nuclear power plants (PLTN) in Indonesia on detikcom and KOMPAS.com as online news media platforms from media conglomerates from 1 August 2022 to 31 August 2023, while also comparing and finding differences in the existing discourse by using the Discourse Network Analysis (DNA) method. The construction of nuclear power plants is in line with the target for nuclear needs in Indonesia to start in 2040 according to the government's energy roadmap through the Ministry of Energy and Mineral Resources, and the global urgency that nuclear power is an alternative clean energy to replace fossil energy in line with the energy transition to achieve the target of zero carbon emissions by 2060. This research showed that the emerging discourse from all news articles on detikcom and KOMPAS.com is supportive of the government to build nuclear power plants in Indonesia. Due to the government's perspective used in the research, the media actually controlled by media conglomerates and politicians have tended to support all programs promoted by the government. It has influenced the news in the owned media or which under the control of these media conglomerates.